Aberrant DNMT1-mediated DACH1 methylation is associated with colorectal adenoma-to-carcinoma progression - Yan Zhang; Yan Zhang; Honggang Liu (Experimental Biology and Medicine)
Colorectal cancer (CRC) remains a major contributor to cancer-related morbidity and mortality. While Dachshund homolog 1 (DACH1) was recognized as a critical regulator in cancer progression, its role in promoting or suppressing tumor development remains a subject of ongoing debate. This study aimed to elucidate the role of DACH1 in CRC progression and its underlying regulation mechanisms. The expression levels of Methyltransferase 1 (DNMT1) and DACH1, as well as its methylation status were assessed through a combination of TCGA data analysis and experimental validation using immunohistochemistry, PCR, methylation-specific PCR, and bisulfite sequencing RCR on 120 clinical samples, comprising normal mucosa, adenomas, and adenocarcinomas. The relationships among them were evaluated using Pearson or Spearman correlation analysis. The associations between the DACH1 and DNMT1 levels and clinicopathological parameters were examined to determine their clinical relevance. A progressive decrease in DACH1 expression and a concomitant increase in DACH1 promoter methylation and DNMT1 expression were observed from normal mucosa to adenoma and adenocarcinoma tissues. Higher DNMT1 expression and lower DACH1 expression were associated with poorer clinical outcomes, including worse tumor differentiation, lymphatic metastasis, and advanced tumor stages. Paired analysis of tissues from the same patient further validated their inverse expression patterns during CRC progression. DNMT1-mediated DACH1 epigenetic silencing plays a critical role in CRC progression, suggesting that the DNMT1-DACH1 regulatory axis may serve as a potential biomarker and therapeutic target in CRC.